1988
DOI: 10.1126/science.3277283
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Flow in Animal Cells

Abstract: A concerted flow of actin filaments associated with the inner face of the plasma membrane may provide the basis for many animal cell movements. The flow is driven by gradients of tension in the cell cortex, which pull cortical components from regions of relaxation to regions of contraction. In some cases cortical components return through the cytoplasm to establish a continuous cycle. This cortically located motor may drive cell locomotion, growth cone migration, the capping of antigens on a lymphocyte surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
343
1
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(369 citation statements)
references
References 35 publications
24
343
1
1
Order By: Relevance
“…A crucial cell module that drives cellular shape changes is the actomyosin cortex beneath the cell membrane, which produces contractile forces that squeeze the cell forward during migration or constrict it during division. The cell cortex is a thin actin network of thickness ∼0.2 μm (3), which is tightly attached to the plasma membrane (4,5). On the molecular scale, contractile forces are generated by myosin II motor proteins, associated into bipolar filaments (6), which use adenosine 5′-triphosphate (ATP) to exert pulling forces on actin filaments.…”
Section: P-eif2αmentioning
confidence: 99%
“…A crucial cell module that drives cellular shape changes is the actomyosin cortex beneath the cell membrane, which produces contractile forces that squeeze the cell forward during migration or constrict it during division. The cell cortex is a thin actin network of thickness ∼0.2 μm (3), which is tightly attached to the plasma membrane (4,5). On the molecular scale, contractile forces are generated by myosin II motor proteins, associated into bipolar filaments (6), which use adenosine 5′-triphosphate (ATP) to exert pulling forces on actin filaments.…”
Section: P-eif2αmentioning
confidence: 99%
“…it, the association between F-actin and intermediate filaments in the apical cytoplasm is suggested to play an important role in maintaining the integrity of epithelial cells (Bray and White 1988;Hollenbeck et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The cytoskeleton in living cells is composed of three separate filamentous networks: microfilaments, micro- tubules, and intermediate filaments (Bray and White 1988;Hollenbeck et al 1989). Fluorescence microscopic studies showed that F-actin shares a similar localization and arrangement in the central canal and choroid plexus in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…A local actin cycle is necessary to support such a flow model; the retrograde flow of cortical F-actin networks being balanced by an approximately equal anterograde diffusion or other flux of actin monomers. An actin cycle of this type has recently been proposed as a general concept for understanding cell surface motility and locomotion in animal cells (9).…”
Section: An Actin Cycle In Growth Conesmentioning
confidence: 99%